1988
DOI: 10.2337/diab.37.4.488
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Axonal Transport of Substance P in Streptozocin-Induced Diabetic Rats: Effects of Sorbinil and Insulin

Abstract: This study measured the accumulation of substance P-like immunoreactivity (SPLI) proximal and distal to 12-h constricting ligatures applied to rat sciatic nerves. There were three separate experiments, and the baseline for each consisted of control and age-matched rats with 3 wk of untreated streptozocin-induced diabetes. We compared the effects of twice-daily insulin treatment, daily sorbinil (25 mg.kg-1.day-1 p.o.), and a combination of both treatments. In untreated diabetic rats the anterograde accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In addition to the normalization of embryonic growth, insulin supplementation to the diabetic mothers prevented the alterations of BDNF, NGF, p75, and IGF-I mRNA and IGF-I protein content in embryos and newborn rats. As already reported in the literature (Tomlison et al, 1988;Di Giulio et al, 1995), SP transport was also normalized by insulin treatment (data not shown).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In addition to the normalization of embryonic growth, insulin supplementation to the diabetic mothers prevented the alterations of BDNF, NGF, p75, and IGF-I mRNA and IGF-I protein content in embryos and newborn rats. As already reported in the literature (Tomlison et al, 1988;Di Giulio et al, 1995), SP transport was also normalized by insulin treatment (data not shown).…”
Section: Resultssupporting
confidence: 87%
“…Peripheral nerve deficits are characterized by reduced nerve conduction (Norido et al, 1984), progressive axonal atrophy accompanied by reduced neurofilament trasport (Vitadello et al, 1985;Medori et al, 1988), and reduction in anterograde axonal transport (Vitadello et al, 1983;Tomlison et al, 1984). The accumulation of sensory axon substance P at a ligature placed along the sciatic nerve is reduced in diabetic rats (Tomlison et al, 1988;Di Giulio et al, 1995). In more chronic diabetes, the nerve content of substance P is also reduced (Robinson et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is reduced retrograde axonal transport of exogenous NGF (Jakobsen et al, 1981;Schmidt et al, 1986) and reduced levels of endogenous NGF-like immunoreactivity (NGF-LI) in several tissues (Hellweg and Hartung, 1990). Two of the well-established gene targets for NGF-those coding for preprotachykinin A (the substance P precursor) and calcitonin gene-related peptide (CGRP) (Lindsay and Harmar, 1989;)-exhibit reduced expression in the sciatic nerve of diabetic rats (Robinson et al, 1987;Tomlinson et al, 1988;Diemel et al, 1992), and this may be secondary to an NGF deficit. In normal rats injection of radiolabelled NGF into the forepaw results in its carriage to cervical sensory ganglia by retrograde axonal transport (Stoeckel et al, 1975); in the hindlimb, sensory fibres of the sciatic nerve capture labelled NGF injected into the gastrocnemius muscle (Koliatsos et al, 1993); and NGF is produced in adult rat skin (Goedert et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Slow anterograde axonal transport of 6-phosphofructokinase activity is deficient in diabetic rats, this deficit is prevented by intensive insulin treatment [9], but is unaffected by treatment with either of two structurally-unrelated aldose reductase inhibitors [9,10]. Fast anterograde axonal transport of substance P is also deficient in rats with streptozotocininduced diabetes mellitus of either 3 weeks' [11] or 9 months' [12] duration. In both cases aldose reductase inhibition attenuated, but did not prevent the deficit, however the deficit was absent in diabetic rats treated with both insulin and an aldose reductase inhibitor [11].…”
mentioning
confidence: 99%